Screening for Type 1 Diabetes in the General Population: A Status Report and Perspective - Sims, Emily K; Besser, Rachel E J; Dayan, Colin; Geno Rasmussen, Cristy; Greenbaum, Carla; Griffin, Kurt J; Hagopian, William; Knip, Mikael; Long, Anna E; Martin, Frank; Mathieu, Chantal; Rewers, Marian; et al. (Diabetes (New York, N.Y.), 2022)
Most screening programs to identify individuals at risk for type 1 diabetes have targeted relatives of people living with the disease to improve yield and feasibility. However, ∼90% of those who develop type 1 diabetes do not have a family history. Recent successes in disease-modifying therapies to impact the course of early-stage disease have ignited the consideration of the need for and feasibility of population screening to identify those at increased risk. Existing population screening programs rely on genetic or autoantibody screening, and these have yielded significant information about disease progression and approaches for timing for screening in clinical practice. At the March 2021 Type 1 Diabetes TrialNet Steering Committee meeting, a session was held in which ongoing efforts for screening in the general population were discussed. This report reviews the background of these efforts and the details of those programs. Additionally, we present hurdles that need to be addressed for successful implementation of population screening and provide initial recommendations for individuals with positive screens so that standardized guidelines for monitoring and follow-up can be established.